Wheat quality: A review on chemical composition, nutritional attributes, grain anatomy, types, classification, and function of seed storage proteins in bread making quality - Khalid, Anam; Hameed, Amjad; Tahir, Muhammad Farrukh (Frontiers in Nutrition, 2023)
Wheat (Triticum aestivum L.) belonging to one of the most diverse and substantial family Poaceae is the principal cereal crop for the greater part of the world population including Pakistan. It is polyploidy in nature, domestically grown cereal throughout the world and a reservoir of approximately one half of the food calories as it is rich in protein, minerals, B-group vitamins in addition to vitamin E, riboflavin, niacin and thiamine, dietary fiber as well as other valuable constituents like protein, minerals (Cu, Mg, Zn, P and Fe) and has become the leading cereal grain, most extensively employed for the bread making due to quantity and quality of its characteristic protein known as gluten hence accomplishes the greater proportion of human’s dietary requirements. The seed-storage proteins of wheat represent an important source of food and energy, being also involved in the determination of bread-making quality. The two groups of wheat grain proteins i.e. gliadins and glutenins have been widely studied so their genetics and biochemistry are fairly well known. Acrylamide gel electrophoresis in the presence of SDS is now the most extensively used method to isolate and illustrate wheat storage proteins. Recent and upcoming concerns comprise of sustaining production and quality of wheat with least with least input of chemicals used in agriculture and emerging lines with improved quality for precise ultimate uses, particularly human diet. This review focuses on the state of art of scientific studies, detailed phytochemical composition, reproduction growth, types, quality and seed storage protein of wheat.